The World Is Not Enough. (2nd January 2018) - Winters, Edward
Abstract: This paper considers the line drawn between art and the everyday; and some attempts to erase it by artists and art theorists. We look at the sensibility of artists who notice and make work from everyday experience. In modernity the conscription of everyday materials and objects to collage and assemblage develops this sensibility within an aesthetic conception of visual art. Looking at Duchamp's readymades, we consider his claim that these objects are chosen with indifference to their aesthetic properties. We then consider the aesthetic requirements of a medium that directs response to works of art. Briefly, with our conception of a medium in mind, we deliberate upon Modernism, Minimalism, and Conceptualism; and the border between the poetic and poetry. We conclude with a lesson to be drawn from Jim Jarmusch's 2016 film, Paterson . Along the way, we cling to some of Kant's insights concerning the fine arts.